(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Despite being useful in pest control, pyrethroids have been found to bioaccumulate in aquatic organisms and in human breast milk and research has shown that pyrethroids are neurotoxic, affect reproductive health and have ability to interfere with the immunological and endocrine systems, they also function as cancer precursors. This study sought to determine the amounts of pyrethroid residue in the soils and some of the most popular food crops, yam and cassava, in order to evaluate food safety using Gas chromatography Mass spectrometry (GC-MS). Cyfluthrin, alpha cypermethrin and beta cypermethrin are pyrethroids found in all the yams and cassava and soils analysed in this study and their values ranged from 9.98mg/kg to 14.45mg/kg in yam farm soil, 8.1mg/kg to 18.46mg/kg in yam samples, 10.25mg/kg to 14.94mg/kg in cassava samples and 6.13mg/kg to 30.6mg/kg in cassava farm soils. The pyrethroid with the highest residue levels in all the samples taken was beta cypermethrin. The health risk was assessed by calculating bioaccumulation factor and comparing Acceptable Daily Intake (ADI) with Food and Agricultural Organization (FAO) recommendations. Bioaccumulation factor of the foods analysed ranged from 0.49 (beta cypermethrin) to 1.68 (alpha cypermethrin) in cassava and 0.56 (cyfluthrin) and 1.07 (alpha cypermethrin) in yams. The pyrethroid residues discovered in the foods in this study exceeded the ADI of pesticides established by FAO, 0.02mg/kg per day; a significant health risk indication. Care should therefore be taken when using these pesticides and consumption of food exposed to pesticides should be discouraged.